On the origin of Iberomaurusians: new data based on ancient mitochondrial DNA and phylogenetic analysis of Afalou and Taforalt populations - (:unkn) unknown (My University, 2017)
The Western North African population was characterized by the presence of Iberomaurusian civilization at the Epiplaeolithic period (around 20,000 years before present (YBP) to 10,000 YBP). The origin of this population is still not clear: they may come from Europe, Near East, sub-Saharan Africa or they could have evolved in situ in North Africa. With the aim to contribute to a better knowledge of the settlement of North Africa we analysed the mitochondrial DNA extracted from Iberomaurusian skeletons exhumed from the archaeological site of Afalou (AFA) (15,000-11,000 YBP) in Algeria and from the archaeological site of Taforalt (TAF) (23,000-10,800 YBP) in Morocco. Then, we carried out a phylogenetic analysis relating these Iberomaurusians to 61 current Mediterranean populations. The genetic structure of TAF and AFA specimens contains only North African and Eurasian maternal lineages. These finding demonstrate the presence of these haplotypes in North Africa from at least 20,000 YBP. The very low contribution of a Sub-Saharan African haplotype in the Iberomaurusian samples is confirmed. We also highlighted the existence of genetic flows between Southern and Northern coast of the Mediterranean.
Keywords: African Research